The interactive effects of high-fiber diets and Ractopamine HCl on finishing pig growth performance, carcass characteristics, carcass fat quality, and intestinal weights - Graham, A.B.; Houser, Terry A.; Tokach, Michael D.; Dritz, Steven S.; Goodband, Robert D.; DeRouchey, Joel M.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
In previous research, feeding pigs high amounts of dried distillers grains with solubles (DDGS) and wheat middlings (midds) has been shown to reduce carcass yield and negatively affect iodine value (IV). The influence of Ractopamine HCl (RAC; Paylean, Elanco Animal Health, Greenfield, IN) on this response is not known; therefore, a total of 575 finishing pigs (PIC 327 × 1050, initially 123 lb) were used in two consecutive 73-d trials to determine the effects of DDGS and midds (high fiber) withdrawal 24 d before harvest in diets with or without RAC on finishing pig growth performance, carcass characteristics, and fat quality. From d 0 to 49, pigs were allotted to 1 of 2 dietary treatments in a completely randomized design based on initial pen weight. The dietary treatments included a corn-soybean meal–based control diet or diets with 30% DDGS and 19% wheat midds. Twelve pens of pigs were fed the corn-soybean meal control diet, and 24 pens were fed the high-fiber diet. During this 49 d period, pigs fed the corn-soybean meal diets had improved (P < 0.0001) ADG and F/G compared with those fed the high-fiber diets. On d 49, pens of pigs were re-allotted to 1 of 6 dietary treatments; pigs remained on the corn-soybean meal diets, switched from the high-fiber diet to corn-soybean meal (withdrawal diet), or were maintained on the high-fiber diet. These 3 regimens were fed with or without 9 g/ton RAC.
Keywords: Swine; Corn; DDGS; Fiber; Finishing pig; Ractopamine HCl; Wheat middlings